Evaluasi Tingkat Keandalan Jaringan Distribusi 20 kV Pada Gardu Induk Bangkinang Dengan Menggunakan Metode FMEA (Failure Mode Effect Analysis) - Rahmad Santoso; Nurhalim Nurhalim (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Reability evaluation has purposed to find out the level of reliability in distribution system. This research conducted at 20 kV radial distribution system in Bangkinang Substation with FMEA (Failure Mode Effect Analysis). The reability calculation will be compared to PT PLN Standart procedure and its target to be WCS (World Class Service). The reability index are used SAIFI (System Average Interruption Frequency Index) and SAIDI (System Average Interruption Duration Index). The method is gathering the data, data proccessing, and analysis. The SAIFI of four feeders in Bangkinang Substation has not reached the PLN standart 68-2 : 1986 which is 3,2 times/years/costumer. For SAIDI that already reached the requirement is 21 hours/years/costumer only Candika Feeder, Pahlawan, and Salo. While, PT PLN Target to get WCS (World Class Service) with 1.2 times/years/costumer for SAIFI and 0.83 hour/years/costumer for SAIDI, all of the feeder in Bangkinang substation still far from the target.Key words : distribution system, reability, FMEA, SAIFI, SAIDI